Impedance Spectroscopy, AC Conductivity, and Conduction Mechanism of Iron(II) Chloride/Polyvinyl Alcohol/Polyvinylpyrrolidone Polymer Blend - Huda AlFannakh (Advances in Materials Science and Engineering)
Polymer blend electrolytes have been prepared using the casting technique. The electrolyte is composed of two polymers polyvinyl alcohol (PVA)/polyvinylpyrrolidone (PVP)) with a fixed ratio (50 : 50) loaded with varied ratios of FeCl2 (0.5, 1, and 2 wt.%). The impedance analysis indicates that the AC conductivity increased as the temperature was following the power law. Nyquist plots for pure and blend composite samples present depressed semicircles at all temperatures. The conduction mechanism of the pure blend sample was based on a hopping mechanism, whereas the ionic conduction was applied to the blend composite sample. The activation energy for blend and blend composite samples was determined, and the two activation regions appeared for blend electrolyte samples. The results indicate a significant improvement in the electrical behavior of the polymeric blend (PVA/PVP) by adding a small weight percentage of FeCl2 salt to the blend samples.